ROLE OF SEA ICE IN THE FORMATION OF ANNUAL CARBON DIOXIDE CYCLE IN THE ARCTIC - Alekseev G.V.; Nagurny A.P. (My University, 2007)
Exchange of carbon dioxide between the atmosphere and the ocean, which absorbs 25–50% of carbon dioxide released during fuel combustion, plays an important role in the global CO2 cycle. At present, it has been established that absorption or emission of CO2 by the World Ocean is irregular in space and variable in different seasons and years. However, the role of the Arctic basin in the global and regional balance of CO2 has not been examined by researchers, because they believed that the ice cover almost completely hampers gas exchange. The possibility of the significant influence of water areas with seasonal or constant ice cover on the regional and even global balance of CO2 has been assumed in some recent publications. The present paper shows that sea ice could play a crucial role in variation of the annual cycle of CO2 concentrations in polar latitudes.